Tea leaf [Camellia sinensis (L.) Kuntze] extract-synthesized silver nanoparticles as antimicrobial agent against foodborne pathogens - Loo, Yuet Ying (2018)
Foodborne illness has emerged as an important public health problem in many countries in the last decade. The main purpose of this research is to study the antibacterial activity of silver nanoparticles against foodborne pathogens. Silver nanoparticles (AgNP) are well-known as antimicrobial agents due to their strong biocidal effect against microbial species. In this study, the synthesis of AgNP using the Chinese tea extracts from Camellia sinensis was reported. The synthesized nanoparticles were characterized using UV-vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and fourier transform infrared (FTIR) spectroscopy. The XRD analysis shows that the synthesized AgNP are of face-centered cubic structure. Well-dispersed AgNP with an approximate size of 4 nm were observed in the TEM image. The antibacterial activity of silver nanaoparticles was tested against 12 foodborne pathogens namely Escherichia coli, Escherichia coli O157:H7, Klebsiella pneumoniae, Staphylococcus aureus, Bacillus cereus, Salmonella Typhimurium, Salmonella Enteritidis, Enterococcus faecalis, Enterococcus durans, Listeria monocytogenes, Bacillus subtilissubsp. spizizenii, and Methicillin-resistant Staphylococcus aureus. The antibacterial activity of AgNPs was determined by using disc diffusion method, resazurin microtitre-plate assay (minimum inhibitory concentration, MIC), minimum bactericidal concentration test (MBC), and time-kill curve assay.The disc diffusion test showed that all the foodborne pathogens were susceptible to AgNPs. The MIC and MBC value of AgNPs against these 12 foodborne pathogens were ranged from 3.9 to 15.6μg/mL. The time kill activity of AgNPs against these foodborne pathogens was tested; the reduction in the number of CFU/ml was >3 log10 units (99.9%) in 1-2 h. This study indicates that AgNPs has antibacterial activity. The toxicity study using the brine shrimp nauplii demonstrated that AgNPs have medium toxic to A. salina (LC50 = 107.52 μg/mL). The applications of AgNPs were done by adding AgNPs into the washing-up liquid as an antibacterial additive in washing the artificially contaminated chopping board. Washing the artificially contaminated chopping board by using washing-up liquid with AgNPs reduced the bacteria count by 1.60 ± 0.11 log10 CFU/g for S. aureus; while for S. Typhimurium, the bacteria count was reduced by 2.90 ± 0.02 log10 CFU/g. The decontamination efficacy of washing using washing-up liquid with AgNPs was found to be significant (P< 0.05) and the most effective way in reducing the microbial contamination in chopping board. This is the first report to demonstratethat the application of AgNPs in washing-up liquid has significant antibacterial activity against foodborne pathogens. Overall, the findings show that AgNPs have strong antibacterial activity and can be an alternative antimicrobial agent.